CLOUD COMPUTING BASED INFRASTRUCTURE IN EDUCATION: INVESTING INTO THE PRIVATE INFRASTRUCTURE OR USING OUTSOURCING SERVICES - Miseviciene, Regina; Kalvaitiene, Daiva; Riskeviciene, Vilma; Ambraziene, Danute; Makackas, Dalius (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The main challenge for higher education in the nearest future is the global competitiveness, as the present global market requires the higher schools to present their courses in the international level. Thus, traditional universities must adapt educational infrastructures in response with the global requirement. Outsourcing of cloud computing based services increased over the years. The solutions allow not only create more effective teaching methods and new communication chances for the whole education society, but also to reduce costs of installing and maintaining programs.Aim of the article is to prepare a cost/benefit case analysis between investing into the private information and communication technology infrastructure and using outsourcing services. This paper focuses attention on cloud computing based information and communication technology infrastructures of two higher education institutions.Research methods include analysis of scientific literature, review of legal institutional documentation and reports and interviews with institutional representatives about education practices.